2014
DOI: 10.1007/s00595-013-0824-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of extremely low birth weight neonates with bowel obstruction within 2 weeks after birth

Abstract: For ELBW neonates with bowel obstruction of unclear etiology, the early and frequent administration of a Gastrografin(®) enema is reasonable. Surgery should be considered if the obstruction lasts beyond approximately 14 days after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The reason for successful meconium evacuation, despite Gastrografin not reaching the distal ileum, in the current study is not exactly known. It is highly probable that the early initiation of therapy and the frequent interventions, which were reported in previous studies [ 13 , 17 , 19 , 29 , 40 ], played important roles; however, it is also possible that our cases had a mild form of MRI. Emil et al [ 29 ] indicated that a 10-day duration of obstruction was the limit for which the medical treatment was effective.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The reason for successful meconium evacuation, despite Gastrografin not reaching the distal ileum, in the current study is not exactly known. It is highly probable that the early initiation of therapy and the frequent interventions, which were reported in previous studies [ 13 , 17 , 19 , 29 , 40 ], played important roles; however, it is also possible that our cases had a mild form of MRI. Emil et al [ 29 ] indicated that a 10-day duration of obstruction was the limit for which the medical treatment was effective.…”
Section: Discussionmentioning
confidence: 82%
“…Eventually, this leads to extrauterine growth restrictions, and may have long-term adverse effects, including short stature and poor neurodevelopmental outcomes [ 12 ]. Reasons for delayed passage may include meconium ileus that is related to cystic fibrosis (CF), and meconium-related ileus (MRI) without CF, which occurs mainly in preterm infants [ 13 ]. Several studies have reported treatment of MRI with saline enemas, glycerin suppositories, and oral contrast agents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, it is recom mended that passing of the contrast agent through the dilated proximal bowel be confirmed by visualization using a radio opaque agent under fluoroscopic control. However, in clinically unstable premature infants, bedside ultrasonographyguided gastrografin enemas are safe and sufficient to diagnose and treat MO 20,21) . Surgical intervention is mandatory in patients with bowel perforation and considered for those with worsening clinical condition and showing progression of abdominal disten sion 22) .…”
Section: Clinical Characteristics and Risk Factors Of Vlbw Infants Wimentioning
confidence: 99%
“…Meconium obstruction in prematurity results from immature or ineffective peristalsis of the fetal intestine, which develops obstructive symptoms predisposing to intestinal perforation if not diagnosed and treated promptly . Owing to the underlying prematurity, clinical decisions on when to convert to surgical treatment in extremely premature infants with meconium obstruction remain controversial . The present case had a potential high risk of intestinal perforation without surgery because repetitive contrast enema was ineffective for improving the distention of the small intestine.…”
mentioning
confidence: 84%